2012
DOI: 10.1590/s1517-83822012000200026
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of the oleaginous microorganisms in Tibetan Plateau

Abstract: Microbial lipids, which are also known as single cell oils (SCO), are produced by oleaginous microorganisms including oleaginous bacteria, yeast, fungus and algae through converting carbohydrates into lipids under certain conditions. Due to its unique environment having extremely low temperature and anoxia, the Tibetan Plateau is amongst the regions with numerous rare ecotypes such as arid desert, salt marsh, alpine permafrost, hot spring, and lawn. By using a rapid, convenient screening method, we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Moreover, two of the psycrotrophic isolates from Antarctica resulted oleaginous. This finding was not surprising since the presence of oleaginous yeasts and molds in extreme cold environments like the Tibetian plateau has already been reported [20]. Although many of the isolates were characterized as oleaginous, only four isolates were able to accumulate a significantly higher amount of intracellular lipids, with levels exceeding the 40% of cell dry weight.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, two of the psycrotrophic isolates from Antarctica resulted oleaginous. This finding was not surprising since the presence of oleaginous yeasts and molds in extreme cold environments like the Tibetian plateau has already been reported [20]. Although many of the isolates were characterized as oleaginous, only four isolates were able to accumulate a significantly higher amount of intracellular lipids, with levels exceeding the 40% of cell dry weight.…”
Section: Discussionsupporting
confidence: 59%
“…The genotypic identification using the 18S rRNA gene sequencing confirmed that this isolate is related to F. solani. In a similar study, Li et al (2012) isolated several Fusarium strains from the Tibetan Plateau with lipid contents ranging from 15Á4 to 27Á6%. Also, Chahal et al (1979) reported that a strain of F. oxysporum could accumulate a lipid content of 24Á3%.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Selective cultivation of environmental 444 microbes that could continue growing for several generations in carbon-free medium using their own 445 stored lipids as the sole carbon source resulted in the discovery that Cryptococcus adeliensis is oleaginous 446 (Li et al , 2012).…”
mentioning
confidence: 99%